Financial Derivatives, Earnings Management, and Firm Performance : Evidence from the Global Financial Crisis - Kapoor, Shashvat (My University, 2019)
The quality of corporate governance and risk management is one of the main determinants of firm performance during economic downturns. The global financial crisis of 2007–08 reduced the global market capitalization by approx. 50%, making it one of the most acute financial crises. Only a few studies have investigated the direct impact of financial derivatives usage and earnings management simultaneously on market performance for non-financial firms during this period. These studies report mixed results on the phenomenon varying based on the sample and the empirical methodology used. This study aims to identify the effect of the two income smoothing techniques on the market performance of non-financial firms during the global financial crisis. It uses a binary variable indicating the use of financial derivatives and the absolute amount of discretionary accruals during a specific year as the main independent variables, while firm performance is measured by a novel variable - the cumulative monthly stock returns during the year. The sample includes 297 firms listed on the S&P 500 index between 2005 and 2009, which allows comparison of results observed during the pre-crisis period and the crisis period. In addition to Pooled OLS, fixed-effects models are used in the regression analysis. The empirical findings suggest that using financial derivatives has a positive impact on firm performance, while the magnitude of discretionary accruals has a negative impact. These relationships are stronger during the crisis period, especially for larger firms and firms with more independent boards. Although the results are robust and of significance to academics as well as practitioners, further research using a larger sample and a longer time horizon may enhance their validity and address any potential endogeneity bias.
Keywords: Derivatives; Earnings Management; Firm Performance; Financial Crisis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance